Characterization of arsenic and selenium species in Portuguese diet as a contribution to selenium protective mechanism against arsenic toxicity - Gueifão, Sandra (2018)
Background and objective(s): Selenium is an essential trace element for human health. Through selenoproteins, it participates in various biological processes such as antioxidant defence, thyroid hormone production and immune responses. The role of Se in the prevention of As – induced toxicity has been documented in several studies. Se-dependent sequestration of As is suggested as a primary mechanism of interaction between Se and As toxic species. To understand the mechanisms involved in the Se/As interactions it is necessary to characterize their presence in foods as principal source of exposure. The aim of this work was to evaluate Se Methionine (SeMet), Selenite (Se (IV)) and Selenate (Se (VI)) and Arsenite (As(III)), Arsenate (As(V)), Dimethylarsinic acid (DMA) and Arsenobetaine (AsB) in fresh and cooked foods representative of the Portuguese Diet. Materials and methods: Speciation analysis was carried out by High Performance Liquid Chromatography (HPLC) coupled to Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Before analysis, samples were extracted using specific extraction procedures for As and Se. Results: More than 90% of the As present in fish samples was in the form of AsB while in rice samples results showed that 80% of the As was present as inorganic forms and 20% as DMA. SeMet was the major Se species in milk and fish samples accounting for 85-90 % of the total Se content. In cabbage Se (IV), Se (VI) and (SeMet) were found. Discussion and conclusion(s): The results showed the suitability of the analytical procedures to achieve an accurate determination of As and Se species in these complex matrices.